Stabilization of human milk fat analog emulsions using milk fat globule membrane material–coated lipid droplets: Structural and physical properties. (15th December 2022) - Liu, Yibo; Cheng, Jinju; Sun, Lina; Li, Xiaodong; Liu, Lu; Ma, Qian; Ma, Chunli; Jia, Zhibin; Zhang, Lihong; Zhang, Qiumei; Leng, Youbin
Abstract: To mimic the human milk fat globule, milk fat globule membrane (MFGM) was used as an emulsifier to coat the lipid droplets for the preparation of the human milk fat analog emulsions (MFEs). The physical properties of MFEs at different pH and ionic strength and digestion properties were evaluated. The results showed that the encapsulation rate of MFEs was more than 90%, and the zeta potential was −18.53 mV. MFGM fragments were adsorbed at the interface of the lipid droplets and remained stably dispersed in the aqueous phase. Aggregation of MFEs occurred at pH of 3.5–5.3 and NaCl ≥50 mM or CaCl2 ≥ 5 mM. MFEs behaved as viscoelastic liquids at a pH < 6.7 and aggregated at a pH < 4.6, thus forming a gel with increased viscosity. In addition, the digestive characteristics of MFEs were closer to that of human milk. Lipid droplets aggregated during the gastric digestion stage; however, some parts of the globule structure remained until the end of the intestinal digestion stage. This study provides a better understanding of emulsifying and digestive properties of MFGM, and MFGM can be exploited to develop emulsions containing MFGM-coated lipid droplets for the design of infant food. Highlights: Encapsulation rate of MFEs was greater than 90%. MFGM fragments were adsorbed at the interface of the fat droplets. The particles were uniformly dispersed in the solution. MFGM-rich ingredients have highly valuable emulsifying properties. Compared to the lipid droplets covered by whey protein, the digestive properties of MFEs more closely that of HM fat.